Convective boiling and condensation in enhanced tubes produced by selective laser melting - Tan, Choon Yong (2018)
This project presents a study on condensation and boiling of R407c inside enhanced tubes fabricated by Selective Laser Melting. The results are compared against a plain SLM tube. The design of the four tubes are five long circumferential pin fins, eight short circumferential pin fins, twisted pin fins and a metallic foam structure. For condensation, the vapour qualities at the inlet and outlet were maintained at 0.9 and 0.3, respectively whereas for boiling, the vapour qualities at the inlet and outlet were maintained at 0.2 and 0.8, respectively. Factors that affects the heat transfer coefficient such as fin height, refrigerant flow direction and mass flux were studied. The results show that saturation pressure, vapour quality, mass flux, refrigerant flow direction and effective heat exchange area have an impact on both condensation and boiling heat transfer. The eight-fin tube showed the highest condensation heat transfer coefficient while the metallic foam tube exhibited the highest boiling heat transfer coefficient. Interestingly, the metallic foam demonstrated poorer condensation heat transfer coefficient although it has the highest heat transfer area.